The System of Revenue Sharing and Fiscal Transfers in China - Wang, Xiao (OECD Economics Department Working Papers, 2013)
The main features of China's current sub-national finance arrangements date back to the 1994 tax reform. China has a multi-level government structure that shares national tax revenues through a system of tax sharing and transfers, and divides spending assignments and responsibilities. Local governments have hardly any discretionary power to modify taxation, though they have some non-tax revenue from fees, levies and penalties. They can also spend the profit from the sale of land-use rights subject to central government restrictions. As the 1994 tax reform recentralised revenues and decision-making power, vertical gaps between revenue and expenditure at sub-national levels have grown. In order to accommodate this, the central government has raised the scale of transfers. Over the past decade, China's transfer policy has addressed the horizontal imbalances and become markedly more redistributive. Nevertheless, fiscal disparities within provinces remain high and are much greater than between regions in OECD countries. The extent of fiscal equalisation within provinces varies, thus affecting the delivery of services. The government's plan to equalise service provision across the country therefore calls for fine-tuning the transfer system and improving local revenue. Some local governments are testing a residential property tax but not in a form that would substantially raise tax revenue. A significant property tax would tend to lower the revenue from the sale of land-use rights and would, in general, improve the fiscal position of those local governments that already have strong budgets. This Working Paper relates to the 2013 OECD Economic Survey of China (www.oecd.org/eco/surveys/china)